Methanol : the basic chemical and energy feedstock of the future : Asinger's vision today - Bertau, Martin, editor; Offermanns, Heribert, editor; Plass, Ludolf, editor; Schmidt, Friedrich, editor; Wernicke, Hans-Jurgen, editor (New York : Springer, 2014)
Includes bibliographical references and indexes